2013
DOI: 10.1002/ange.201300616
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of 2,2‐Disubstituted Tetrahydrofurans: Palladium‐Catalyzed [3+2] Cycloadditions of Trimethylenemethane with Ketones

Abstract: An approach to 2,2-disubstituted 4-methylenetetrahydrofurans has been developed utilizing a cycloaddition of trimethylenemethane with aryl ketones, with formation of the products in up to 96% yield and 95% ee. The reaction is catalyzed by palladium in the presence of a phosphoramidite ligand possessing a stereogenic phosphorus, where only a single epimer at phosphorus yields the active catalyst. The identity of this epimer and the origin of its effect on reactivity are discussed. Keywords trimethylenemethane c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 35 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Additionally, they employed as chiral ligands in various asymmetric reactions. Examples are metal‐catalyzed stereoselective reduction of ketones, ketimines and alkenes, various cycloadditions, addition of boronic acids and organotrifluoroborates to alkenes, asymmetric ruthenium‐catalyzed metallo‐ene reaction and Suzuki‐Miyaura coupling …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, they employed as chiral ligands in various asymmetric reactions. Examples are metal‐catalyzed stereoselective reduction of ketones, ketimines and alkenes, various cycloadditions, addition of boronic acids and organotrifluoroborates to alkenes, asymmetric ruthenium‐catalyzed metallo‐ene reaction and Suzuki‐Miyaura coupling …”
Section: Methodsmentioning
confidence: 99%
“…In addition, N-phosphorylpyrrolidines are employed as chiral ligands in various asymmetric reactions. Examples include metal-catalyzed stereoselective reductions of ketones, 14,15 ketimines 16 and alkenes, [17][18][19] various cycloadditions, [20][21][22][23] additions of boronic acids 24 and organo-trifluoroborates 25 to alkenes, asymmetric ruthenium-catalyzed metallo-ene reactions 26 and Suzuki-Miyaura couplings. 27 In spite of this, methods for the synthesis of these compounds have never been reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Despite the development of elegant strategies to access chiral trifluoromethyl-substituted tertiary alcohols, methods that directly assemble 2,2-disubstituted dihydrofurans in asingle step from available fluorinated ketones would be of high interest (Scheme 1B). [8] Our group has al ong-standing interest in [3+ +2] cycloadditions of trimethylenemethane (TMM) donors with electron-deficient acceptors. [9] Recently,w eh ave demonstrated that the s-electron-withdrawing properties of the CF 3 group could be used to promote the [3+ +2] cycloaddition, affording cyclopentanes bearing aq uaternary center, albeit without absolute control of chirality (Scheme 1C).…”
mentioning
confidence: 99%